The Role of Cultural Value Orientations and Sexual Desire in Predicting Cybersex Behavior in Unmarried Young Adults - Virgon Hartoyo; Juneman Abraham (ANIMA Indonesian Psychological Journal, 2015)
The presence of Internet technology has opened up the emergence of new forms of sexual behavior, such as cybersex, which seems more massive nowadays. Regardless of the merits intended by the facilitating technology, in the context of Indonesian culture in which premarital sexual behavior (especially cybersex) is perceived as immoral, it is important to determine predictors of cybersex in order to minimize (or possibly eliminate) its negative impacts. This predictive-correlational designed study on 333 unmarried young adults participants (144 males, 189 females; mean of age = 20.724 years old, standard deviation of age = 1.902 years) employed the five dimensions of Hofstede‟s cultural value orientations (at individual level) and sexual desire as the predictors. The finding of this study was that only the long term orientation and sexual desire play significant roles in predicting cybersex, in positive ways; while four other cultural value orientations (power distance, uncertainty avoidance, masculinity/femininity, and collectivism/individualism) are not able to predict it.